A visit to the domed churches of Charente, France, by the Architectural... - Architectural... (Wikimedia Commons, 1880)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Licence No known copyright restrictions via Wikimedia Commons
Keywords: histoire; iconographie; gravure; photographie; wikimedia commons